In vitro study of NCs/dyes complexes accumulation and dyes release kinetics in rat hepatocytes - Yefimova, S.L.; Tkacheva, T.N.; Kavok, N.S.; Klochkov, V.K.; Sorokin, A.V. (Functional Materials, 2015)
Using fluorescence microspectoscopy and FRET-labeling of various nano-scale carriers (NCs) the efficiency and kinetics of NCs/dye molecules complexes accumulation in living cells and dye release have been studied. Organic liposome vesicles and inorganic nanoparticles (CeO₂ and GdYVO₄:Eu³⁺) were used as NCs. NCs/dyes complexes formed in aqueous solutions have been characterized. It has been shown that NCs based on GdYVO₄:Eu³⁺ nanoparticles exhibit the most effective accumulation in cells and provide very fast release of the lipophilic cargo (dyes molecules). Lipophilic compound (cholesterol) embedded into the NCs/dyes complexes decreases noticeably the rate of lipophilic dyes release and reduces the affinity of the complex interaction with hepatocytes. GdYVO₄:Eu³⁺ NPs could be used as a nano-scale platform for controlled intracellular delivering of hydrophobic agents.